2015
DOI: 10.1002/j.0022-0337.2015.79.8.tb05987.x
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Dental Students in Spain to Identify Potentially Malignant Disorders and Oral Cancer

Abstract: The aim of this study was to assess the ability of students at the School of Dentistry, Complutense University of Madrid, Spain, to diagnose oral cancer and other potentially malignant disorders, as well as to compare their ability at different stages of the learning process and evaluate their knowledge retention. Students were surveyed after they had studied oral medicine and oral pathology at two time points: midway through and near the end of their studies. The survey consisted of questions about 40 photogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 27 publications
(20 reference statements)
0
19
0
1
Order By: Relevance
“…The early detection of oral cancer is positively associated with a better prognosis, therefore it is imperative that dental students be sufficiently trained and competent in the diagnosis and multidisciplinary treatment of the disease 4 . A dentist's ability to identify PMLs and initial malignant lesions depends largely on the knowledge and skills they acquire during their undergraduate course 16,17 . In the present study undergraduate dental students' levels of knowledge about oral cancer were considered reasonable, which is consistent with previous reports 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…The early detection of oral cancer is positively associated with a better prognosis, therefore it is imperative that dental students be sufficiently trained and competent in the diagnosis and multidisciplinary treatment of the disease 4 . A dentist's ability to identify PMLs and initial malignant lesions depends largely on the knowledge and skills they acquire during their undergraduate course 16,17 . In the present study undergraduate dental students' levels of knowledge about oral cancer were considered reasonable, which is consistent with previous reports 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…This comes in contrast to what was reported in the study by Burzynski et al, who reported a lack of knowledge and skills perceived by graduating students regarding oral cancer detection [8]. Cerero Lapiedra et al also suggested the need to increase the focus on cancer education in the dental curriculum to enhance students' skills in identifying potentially malignant disorders [14]. Joseph et al assessed oral cancer knowledge among undergraduate dental students and demonstrated the need for organized teaching programs [15].…”
Section: Discussionmentioning
confidence: 76%
“…Indeed, the need for further education is also supported by the findings of others 13,19 . This point was also made at the consensus undergraduate curriculum in Oral Medicine in the United Kingdom and Republic of Ireland, where the importance of management of mucosal pathologies as a part of oral health care was discussed 20,21 . Similarly, other studies concluded that more contact with patients with oral pathologies are needed 22,23 …”
Section: Discussionmentioning
confidence: 81%